FAKTOR FAKTOR MOTIVASI PENDIDIK DAN TENAGA KEPENDIDIKAN DALAM KEGIATAN PENDIDIKAN DAN PENGEMBANGAN MADRASAH DI MADRASAH IBTIDAIYAH DARUL ILMI SUMBAWA BARAT - ISLAHUDDIN (UNISAN JURNAL, 2024)
This study aims to determine curriculum management and the implementation of curriculum management in improving the quality. This research includes qualitative research using interview, observation and document methods. The results of this study indicate that: 1) Curriculum management in improving the quality of learning is the application of 2013 curriculum components, applying the stages in curriculum preparation, making superior strategies and programs and creating cooperation from all parties who build, there are students who achieve achievements so that curriculum management in Madrasah Ibtidaiyah can improve the quality of learning, 2) The implementation of curriculum management in improving the quality of learning runs smoothly and educators use various models, methods and learning media, the implementation of curriculum management is compatible with improving the quality of learning, 3) Supporting factors for curriculum management include sincere intentions and sincere from educators, professional educators and have broad insight, educator loyalty and actively develop methods along with the development of technology and good communication between components of madrasa management. The inhibiting factors for curriculum management include the environment of students who are less supportive in science, especially families, lack of knowledge for parents, limited funds in fulfilling facilities and infrastructure and following technological developments to assist the learning process.